Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.4 - Adding and Subtracting Rational Expressions with Different Denominators - Exercise Set: 75

Answer

$\frac{6x^{2}-5x-3}{x(x+1)(x-1)}$

Work Step by Step

$\frac{3}{x}$ -$\frac{2x}{x^{2}-1}$+$\frac{5}{x+1}$= $\frac{3}{x}$ -$\frac{2x}{(x+1)(x-1)}$+$\frac{5}{x+1}$= $\frac{3(x+1)(x-1)}{x(x+1)(x-1)}$ -$\frac{2xx}{x(x+1)(x-1)}$+$\frac{5x(x-1)}{x(x+1)(x-1)}$= $\frac{3(x+1)(x-1)-2xx+5x(x-1)}{x(x+1)(x-1)}$ = $\frac{3(x^{2}-1)-2x^{2}+5x^{2}-5x}{x(x+1)(x-1)}$ = $\frac{3x^{2}-3+3x^{2}-5x}{x(x+1)(x-1)}$ = $\frac{6x^{2}-5x-3}{x(x+1)(x-1)}$ =
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.